Plants as a Source of Green Corrosion Inhibitors: The Case of Gum Exudates from Acacia Species (A. drepanolobium and A. senegal) - Buchweishaija, J (Tanzania Journal of Science, 2009)
The inhibitive performance of gum exudates from Acacia drepanolobium and Acacia senegal from Tanzania, towards the corrosion of mild steel in fresh water has been investigated. The experimental methods include potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) studies. The results indicate that gum exudates (Acacia drepanolobium and Acacia senegal) exhibit good inhibition characteristics to corrosion on mild steel under fresh water medium and the inhibition efficiency of up to 90.7% and 99.7% respectively was attained at 30 oC. Furthermore, the studies have shown that the inhibition performance remained above 90% on both Acacia exudates independent of the raise in temperature. Polarization measurements revealed that the investigated inhibitors are mixed type for mild steel corrosion in fresh water with significant reduction of anodic current densities (this sentence is not clear). The results obtained in this work show that these gum exudates of Acacia senegal and Acacia drepanolobium can serve as effective green inhibitors for the corrosion of mild steel in fresh water systems.